Domestic Violence Against Children in Islamic Perspective - Lia Yuliana (Trigin Publisher, 2020)
Acts that have the smell of violence committed by anyone will only give birth to emotional and psychological misery for the other person who is the goal or target. Acts of violence committed by anyone will only give birth to misery for the other party. Violent behavior can occur anywhere, in public places (public), at school, in the office and at home, even in places where violence seems impossible. Domestic violence is certainly different from violence in other places, be it the perpetrator. the causative factors, the process of forming violence, the forms of violence and their intensity. Domestic violence is violence that occurs in the household where usually the male sex (husband) abuses verbally or physically against women or children. Domestic violence perpetrated by mothers and fathers against their children is interesting to study which aims to obtain or obtain information about domestic violence as a reflection of the differences between men and women so as to encourage the formation of violence against children in the family.